2022
DOI: 10.15537/smj.2022.43.9.20220291
|View full text |Cite
|
Sign up to set email alerts
|

Are women diagnosed with early pregnancy loss at risk for anxiety, depression, and perinatal grief?

Abstract: Objectives: To examine the effects of early pregnancy loss on emotions such as depression, grief, or a sense of hopelessness, while investigating different types of diagnoses, hospital stays, and treatments. Methods: A prospective cohort epidemiological study was carried out in Bursa Yuksek IhtisasTraining and Research Hospital, Bursa, Turkey, between January and September 2019. The study included women diagnosed with early pregnancy loss classified into 3 groups: missed abortus, anembryonic pregnancy, and spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The PGS has been used in research to measure perinatal grief following pregnancy loss, including grief during a pregnancy subsequent to perinatal loss (Barr & Cacciatore, 2008;Beauquier-Maccotta et al, 2022;Kulathilaka et al, 2016). It has also been used to determine the relationships among perinatal grief and factors such as number of pregnancy losses, gestational age at time of loss, religiosity, ruminative thoughts, posttraumatic symptoms, and posttraumatic growth (Cowchock et al, 2010(Cowchock et al, , 2011Gozuyesil et al, 2021;Krosch & Shakespeare-Finch, 2017;Ozgen et al, 2022;Purandare et al, 2012;Penelo et al, 2017). In experimental studies, the PGS has been used to assess the effectiveness of clinical interventions (Fernlund et al, 2021;Johnson & Langford, 2015).…”
Section: Meta-analysis Of Pgs -Short Form (Svpgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The PGS has been used in research to measure perinatal grief following pregnancy loss, including grief during a pregnancy subsequent to perinatal loss (Barr & Cacciatore, 2008;Beauquier-Maccotta et al, 2022;Kulathilaka et al, 2016). It has also been used to determine the relationships among perinatal grief and factors such as number of pregnancy losses, gestational age at time of loss, religiosity, ruminative thoughts, posttraumatic symptoms, and posttraumatic growth (Cowchock et al, 2010(Cowchock et al, , 2011Gozuyesil et al, 2021;Krosch & Shakespeare-Finch, 2017;Ozgen et al, 2022;Purandare et al, 2012;Penelo et al, 2017). In experimental studies, the PGS has been used to assess the effectiveness of clinical interventions (Fernlund et al, 2021;Johnson & Langford, 2015).…”
Section: Meta-analysis Of Pgs -Short Form (Svpgs)mentioning
confidence: 99%
“…Following unexpected pregnancy loss, women report feelings of grief, guilt, anger, anxiety, depression, shock, emotional pain, ruminative thoughts, and maladaptive cognitions (Camacho-Ávila et al, 2019; Gausia et al, 2011; Gozuyesil et al, 2021; Kokou-Kpolou et al, 2018; Ozgen et al, 2022; Punaglom et al, 2022; Sutan & Miskam, 2012; Testoni et al, 2020). Besides the emotional aspects of loss, consequences of perinatal loss include strained social relationships with spouse and the spousal family, changed view of subsequent pregnancies, social isolation, and social pressure (Furtado-Eraso et al, 2020; Gausia et al, 2011; Roberts et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The most common adverse outcomes of pregnancies are pregnancy loss and preterm birth [ 1 ]. A pregnancy loss, also called a miscarriage or spontaneous abortion, is generally defined as a nonviable intrauterine pregnancy before 20 weeks of gestation [ 2 ], and in various countries, it affects approximately 15%–20% of pregnancies [ [3] , [4] , [5] ]. The etiology of miscarriage is multifactorial and includes genetic abnormalities, infections, immunological and implantation disorders, uterine and endocrine abnormalities, and lifestyle factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported short-term anxiety to affect approximately 20–40%, and depression 15–55% of women who have suffered an EPL ( 28 , 29 ). A more recent study showed even greater morbidity, with 73% of their sample presenting symptoms of depression, and 100% with moderate symptoms of anxiety ( 30 ). These studies seem to support some early studies reporting that anxiety might be more frequent and have higher morbidity than depression in this population ( 18 , 31 ).…”
Section: Introductionmentioning
confidence: 99%